Efektivitas Edukasi Donor Darah Melalui Media Video pada Keluarga Pelajar Mahasiswa Indonesia Bolaang Mongondow Raya Yogyakarta - Srinopiyanti Labeddu; Nurpuji Mumpuni; Nur'Aini Purnamaningsih (Jurnal Sains & Kesehatan, 2023)
The limited number of donors can be caused by a lack of information about blood donors. Knowledge is one aspect of knowing human behavior. To increase students' knowledge, they need a learning media that can describe real physical concepts such as video education. The objective of this study was to describe the effectiveness of blood donor knowledge education through video media at the Indonesian Bolaang Mongondow Student Families Raya Yogyakarta. This research was a quantitative descriptive research with a Quasi-Experimental method which was carried out with a pretest-posttest. The sample is 56 respondents and the sample is taken using the Random Sampling technique. The results showed that the level of knowledge about blood donation prior to video education found that the respondents classified as having a good level of knowledge, 15 people (26.8%), enough 26 people (46.4%), less 15 people (26.8%). While the level of knowledge of blood donors after educational video knowledge was good for 45 people (80.4%), enough for 10 people (17.9%) and less for 1 person (1.8%). The pretest average value of 56 respondents was 65.11 and the posttest average value was 88.59. The effectiveness of video education based on gender characteristics obtained very small results, namely men (difference in the mean pretest and posttest 24.85) and women (difference in the average pretest and posttest 24.24) it can be said that video education is not influenced by gender sex. Based on the characteristics of the most effective age 21-25 years (difference in the average pretest and posttest 23.97) can be said to be influenced by age. Based on the characteristics of the most effective level of education SMA/SMK (difference in the average pretest and posttest of 35) it can be said that it is influenced by the level of education. The results of the paired t test showed that there were significant differences in the level of knowledge about blood donors before and after education using video media with the Sig value obtained. 0.000. Education on blood donor knowledge through videos is effective in increasing knowledge about blood donation.